Anesthetic regimen for cardiac function evaluation by echocardiography in mice: comparison between ketamine, etomidate and isoflurane versus conscious state. (October 2013) - Lairez, Olivier; Lonjaret, Laurent; Ruiz, Stéphanie; Marchal, Pauline; Franchitto, Nicolas; Calise, Denis; Fourcade, Olivier; Mialet-Perez, Jeanne; Parini, Angelo; Minville, Vincent
Mice with genetic alterations are used in heart research for the extrapolation of human diseases. Echocardiography is an essential tool for evaluating cardiac and hemodynamic functions in small animals. The purpose of this study was to compare the effect of different anesthetic regimens and the conscious state on the evaluation of cardiac function by echocardiography. Mice were examined in the conscious state after three days of training, and then for a 7 min period after a single intraperitoneal injection of ketamine at 100 mg/kg, etomidate at 10, 20 or 30 mg/kg, or after inhalation of isoflurane at 1.5% with or without a short period of induction with isoflurane 3%. Intra- and inter-observer variabilities were assessed. The operator's comfort was also assessed. Heart rate, left ventricular end diastolic diameter, fraction shortening and cardiac output were measured using echocardiography. Ketamine at 5 and 7 min after induction and isoflurane at 3, 5 and 7 min after induction provided good anesthetic conditions and a quick awakening time, and did not influence cardiac performance, whereas the conscious state was associated with a non-physiological sympathetic activation and other anesthetic drugs induced a significant decrease in heart rate. Etomidate 10 mg/kg and 20 mg/kg were not enough to provide adequate anesthesia. Etomidate 30 mg/kg induced a good anesthetic condition but influenced cardiac performance and had a long awakening time. Our results indicate that ketamine and isoflurane with a short induction period are better anesthetic drugs than isoflurane without induction or etomidate for evaluating cardiac function in healthy mice.